2002
DOI: 10.1038/sj.bjc.6600174
|View full text |Cite
|
Sign up to set email alerts
|

Cancer testis antigens expression in mesothelioma: role of DNA methylation and bioimmunotherapeutic implications

Abstract: Recent evidences suggest that malignant mesothelioma may be sensitive to immunotherapy; however, little is known about malignant mesothelioma-associated tumour antigens. Focusing on cancer/testis antigens, the expression of well-characterised immunogenic tumour-associated antigens was investigated in malignant mesothelioma cells. At variance with MAGE-4 and NY-ESO-1, malignant mesothelioma cells frequently expressed MAGE-1, -2 and -3, GAGE 1-2, GAGE 1-6, SSX-2 and SSX 1-5, and distinct malignant mesothelioma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 18 publications
5
63
0
2
Order By: Relevance
“…In addition, Janssen et al (18) showed a strong 5-aza-CdR-induced MAGE-A1 expression, which did not correlate with the number of demethylated CpG sites in the Ets motif. Moreover, our findings are comparable with the results published by Sigalotti et al (27), who reported that the 5-aza-CdR-mediated overall DNA demethylation of CpG dinucleotides ranged from 6% to 12%. Similar to our data, Suyama et al (21) failed to detect a clear relation between DNA demethylation of CpG dinucleotides in both Ets sites of the MAGE-A1 promoter and its transcriptional expression in different 5-aza-CdR-stimulated cell lines.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition, Janssen et al (18) showed a strong 5-aza-CdR-induced MAGE-A1 expression, which did not correlate with the number of demethylated CpG sites in the Ets motif. Moreover, our findings are comparable with the results published by Sigalotti et al (27), who reported that the 5-aza-CdR-mediated overall DNA demethylation of CpG dinucleotides ranged from 6% to 12%. Similar to our data, Suyama et al (21) failed to detect a clear relation between DNA demethylation of CpG dinucleotides in both Ets sites of the MAGE-A1 promoter and its transcriptional expression in different 5-aza-CdR-stimulated cell lines.…”
Section: Discussionsupporting
confidence: 83%
“…Whereas reverse transcription-PCR analysis showed a small effect of trichostatin A on transcription, transfection studies showed that trichostatin A was able to significantly up-regulate promoter-driven luciferase activity of the methylated and even unmethylated reporter plasmids containing each of the four promoter fragments with the exception of the methylated MAGE-A3 construct. In agreement with previous studies (25,27), DNA methylation of transfected reporter constructs could strongly down-regulate promoter activity, which correlated to the methylation-dependent regulation of these genes. Whereas the methylation of the rare HpaII CCGG motifs in the promoters was sufficient to down-regulate the activity, the methylation by the SssI methylase had a negligible effect.…”
Section: Discussionsupporting
confidence: 77%
“…One of the major interests in CT antigens stems from their potential use in cancer vaccines, and several of them have been used in polyvalent vaccine trials with variable success Sigalotti et al, 2002). Although the lack of humoral immunity in PDAC patients and the expression of SPAG1 in several normal tissues would probably hamper a similar utility, further studies would need to be undertaken in order to completely exclude the validity of SPAG1 in such an immunotherapeutic approach.…”
Section: Spag1 In Pancreatic Adenocarcinomamentioning
confidence: 99%
“…These are the GAGE (G antigen 7) family (43), the MAGE (44 -48) family of melanoma antigens, and the genes residing at the synovial sarcoma X breakpoint, SSX2-4 (49,50). It is well documented that the MAGE (44 -46) and GAGE family of genes as well as SSX2 are controlled by DNA methylation and are induced by DNA-demethylating agents (51). The up-regulation of genes identified by gene array analysis was verified by semiquantitative RT-PCR shown in Fig.…”
Section: Comparison Of the Kinetics Of Demethylation Of The Tumor Supmentioning
confidence: 99%